2018
DOI: 10.1007/s11033-018-4351-0
|View full text |Cite
|
Sign up to set email alerts
|

Construction strategies for developing expression vectors for recombinant monoclonal antibody production in CHO cells

Abstract: Recent years have seen the use of recombinant proteins in the treatment of different diseases. Among them, monoclonal antibodies (mAbs) are currently the fastest growing class of bio-therapeutic recombinant proteins. Chinese hamster ovary (CHO) cells are the most commonly used host cells for production of these recombinant mAbs. Expression vectors determine the expression level and quality of recombinant mAbs. Currently, few construction strategies for recombinant mAbs expression vectors in CHO cells have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…In the current study, we created a novel hypoxia responding cell system in CHO production cells based on HRE elements and cellular oxygen sensing proteins. We were able to demonstrate substantial improvement of recombinant protein production under hypoxic process conditions using a vector based system which can be used without time- and cost-intensive host cell modifications in industrial settings ( Li et al, 2018 ). Specifically, we first verified the conservation of the hypoxia-responsive pathway in CHO cell lines, functionally analyzed HREs from VEGF and EPO genes and then created hypoxia-responsive expression vectors.…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, we created a novel hypoxia responding cell system in CHO production cells based on HRE elements and cellular oxygen sensing proteins. We were able to demonstrate substantial improvement of recombinant protein production under hypoxic process conditions using a vector based system which can be used without time- and cost-intensive host cell modifications in industrial settings ( Li et al, 2018 ). Specifically, we first verified the conservation of the hypoxia-responsive pathway in CHO cell lines, functionally analyzed HREs from VEGF and EPO genes and then created hypoxia-responsive expression vectors.…”
Section: Introductionmentioning
confidence: 99%
“…Controlling the LC:HC peptide ratio is essential to the kinetics of mAb formation. It was reported that excess LC and an LC:HC ratio of more than 1.5 are favored since incompletely formed HCs can cause the mAb clones to aggregate and have inconsistent glycosylation (Ahmadi et al, 2017;Ho et al, 2013a;Ho et al, 2013-b;Li et al, 2018). The DNA fragments are then joined together to the plasmid by the enzyme ligase, such as T4 DNA ligase, or by overlap extension PCR and cloned (Haryadi et al, 2015;Voronina et al, 2016).…”
Section: Mammalian Expression Vectors and Recombinant Dna Technologymentioning
confidence: 99%
“…Compared with prokaryotic, yeast and insect cells, CHO cells have the following advantages ( Khan 2013 ): 1) CHO cells can grow under the adhere and suspension state with high cell density, which are suitable for large-scale industrial production ( Lai et al, 2013 ): 2) CHO cells are less sensitive to human virus infection ( O'Flaherty et al, 2020 ): 3) The expressed proteins have high similarity with natural proteins in terms of molecular structure, physicochemical properties and biological functions, and the glycosylation is also more similar to that of human-derived cells due to the lack of immunogenic α-galactose epitopes ( Ghaderi et al, 2012 ): 4) CHO cells are fibroblasts with low endogenous protein secretion, which is beneficial to the isolation and purification of recombinant proteins. ( Mohan et al, 2008 ; Li et al, 2018 ). In addition, by constructing DNA methyltransferase-deficient CHO cells, the stability of expression for the recombinant protein can be enhanced by inactivating DNA methylation ( Jia et al, 2018 ; Wang et al, 2019 ).…”
Section: Mammalian Cells and Expression Vectorsmentioning
confidence: 99%